Clustering of health and oral health-compromising behaviours among adolescents in Kedah / Nurul Izzah Ali - Nurul Izzah, Ali (2019)
Health behaviours tend to cluster together among individual. Research has shown that health-compromising behaviours, for example smoking and high sugar consumption; and oral health-compromising behaviours, such as poor tooth brushing frequency and irregular dental attendance, tend to cluster together in specific patterns. Co-occurrence of multiple health and oral health-compromising behaviours increases the risk of mortality and morbidity. Studies also reported that those behaviours commonly start during adolescence and can extend into adulthood. This study aimed to determine the prevalence, the clustering pattern of health and oral health-compromising behaviours amongst selected adolescents in Kedah, and its determining factors. A cross-sectional study that employed a stratified cluster random sampling method was conducted among selected adolescents aged 13 and 16 years old, who attended public and private schools in four districts in Kedah. Validated self-administered questionnaires were distributed to assess multiple health and oral health-compromising behaviours namely dietary intake, physical activity and sedentary behaviour, smoking status, alcohol consumption, drug use, physical fighting, bullying, use of electronic media communication, frequency of tooth brushing, use of fluoridated toothpaste, and flossing behaviour. Using the Statistical Program for Social Sciences version 23, the descriptive statistics, Phi pairwise correlations, Hierarchical Agglomerative Cluster Analysis (HACA), and Poisson regression analysis were performed. A total of 2983 respondents completed this survey, which comprised of females (54.1%), Malays (86.9%), and those who studied in the public schools (67.2%) and resided in urban areas (53.8%). Most of the respondents had low milk/milk products intake (89%), were physically inactive (81%), had poor oral iii health behaviours (79.9%), ate inadequate vegetables (72%) and fruits (53.1%) intake, had high sugar intake (58.7%) and sedentary behaviours (57.1%). Two broad clusters of health-compromising behaviours were identified. The first cluster named as high risk behaviours, consists of respondents with high acidic food intake, low intake of plain water, high social media addiction, smokers, alcohol and drug users, and had been involved in bullying and physical fighting. The second cluster named as poor adherence to preventive behaviours, included respondents with high sugar intake, low intake of vegetables, fruits and milk/milk products, poor oral health behaviours, had sedentary behaviours, were physically inactive and were breakfast skippers. In term of clustering count, almost one-fifth of respondents had seven (22%), six (21.3%) and eight (16.8%) health and oral health-compromising behaviours. Mean clustering count of health and oral health-compromising behaviours was significantly differed by gender (p=<0.001) and parental educational levels (p=<0.001), and was significantly associated with life satisfaction (p=<0.001) and self-confidence (p=<0.001) of the respondents. Age, mother’s educational level, life satisfaction and self-confidence were the factors associated with the mean clustering count of health and oral health-compromising behaviours. Health intervention programme for adolescent should focus on a cluster of risky behaviours and its associated factors.